The global competition for talent : mobility of the highly skilled - Organisation for Economic Co-operation and Development (OECD, 2008)
Summary (s. 9-16).
Keywords: aivovienti; tutkimus- ja kehittämistoiminta : OECD-maat; työvoiman liikkuvuus; akateeminen työvoima; asiantuntijat